El katechon en su primer contexto: 2 Tesalonicenses 2,1-17 = Abweichender Titel: The katechon in its First Context : 2 Thessalonians 2,1-17 - Pereira Delgado, Álvaro (Cauriensia, 2025)
Current political philosophy frequently uses katechon, a Pauline term that denotes the existence of a temporary force that restrains the manifestation of evil while at the same time postponing the triumph of good. This article investigates the first meaning of katechon by analyzing the communicative context of 2 Thessalonians, particularly the articulation of 2 Thessalonians 2:1-17, which provides the context for the term. It specifically examines the meaning, historical referent, and pragmatic function of the expression. The final section draws conclusions that aim to guide the contemporary appropriation of this concept. The text of 2 Thessalonians 2:1-17, rooted in the Jewish apocalyptic tradition, presents a panoramic view of history from the perspective of the God and Father of the Messiah Jesus. In this depiction of the time of the end, the author of 2 Thessalonians employs the katechon to prevent believers from fleeing or misrepresenting their reality. His intent is to encourage them to persevere in their historical present, which is still under threat from the forces of evil, while assuring them that the history is ultimately in God's hands.